2021
DOI: 10.3389/fmed.2021.655404
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Diagnostic Endoscopy in Inflammatory Bowel Diseases: From High-Definition to Molecular Endoscopy

Abstract: High-definition endoscopy is one essential step in the initial diagnosis of inflammatory bowel disease (IBD) characterizing the extent and severity of inflammation, as well as discriminating ulcerative colitis (UC) from Crohn's disease (CD). Following general recommendations and national guidelines, individual risk stratification should define the appropriate surveillance strategy, biopsy protocol and frequency of endoscopies. Beside high-definition videoendoscopy the application of dyes applied via a spraying… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Still, it is difficult to accurately diagnose intraepithelial neoplasia (IN) in UC accurately because of lacking cellular resolution and subsurface imaging. Confocal laser endomicroscopy (CLE) and endocytoscopy (EC) are promising tools that enable the acquisition of microstructural objects (e.g., capillaries, villiform structure, crypt, goblet, or epithelial cells, nucleus and cytoplasm), representing that endoscopy will shift from macro to micro, and from surface to deep [ 141 ]. As early as 2007, several studies have indicated that CLE could increase the diagnostic yield of INs in UC patients [ 142 ], which was later reported in 2008 [ 143 ].…”
Section: Surveillance For Crc In Ucmentioning
confidence: 99%
“…Still, it is difficult to accurately diagnose intraepithelial neoplasia (IN) in UC accurately because of lacking cellular resolution and subsurface imaging. Confocal laser endomicroscopy (CLE) and endocytoscopy (EC) are promising tools that enable the acquisition of microstructural objects (e.g., capillaries, villiform structure, crypt, goblet, or epithelial cells, nucleus and cytoplasm), representing that endoscopy will shift from macro to micro, and from surface to deep [ 141 ]. As early as 2007, several studies have indicated that CLE could increase the diagnostic yield of INs in UC patients [ 142 ], which was later reported in 2008 [ 143 ].…”
Section: Surveillance For Crc In Ucmentioning
confidence: 99%
“…62 Endoscopic technology, artificial intelligence, and deep learning have the potential to revolutionize our surveillance further and some iterations of these are already in the clinical arena. 45,63 Funding None.…”
Section: Future Directionsmentioning
confidence: 99%
“…In IBD, CLE was used for structural and functional assessment of the intestinal epithelium, characterisation and classification of inflammatory activity and mucosal healing (MH) in active disease, dysplasia detection and molecular imaging for precision medicine. 3,34,35 The assessment of MH in IBD was a further application of CLE since it could accurately distinguish between patch/mild inflammation and MH.…”
Section: Cle Is a Highly Innovative Endoscopic Technique As It Provid...mentioning
confidence: 99%
“…In IBD, CLE was used for structural and functional assessment of the intestinal epithelium, characterisation and classification of inflammatory activity and mucosal healing (MH) in active disease, dysplasia detection and molecular imaging for precision medicine. 3 , 34 , 35 …”
Section: Confocal Laser Endomicroscopymentioning
confidence: 99%